Dynamic Fash Enterprise: Rebar Tie Gun / Mohamad Haziq Suliaman [et al.] - Suliaman, Mohamad Haziq; Azizan, Mohd Aqmarul Hisham; Sunawan, Muhd Salihan; Ahmad Kaman, Mohamad Syafiq; Asrin, Faiz (2017)
Rebar Tie Gun is a business that can be categorized as Small Medium Enterprise (SME) which provide construction services to the customer. We are specialized in helping contractors to shorten their project.